R&D, Embodied Technological Change and Employment: Evidence from Italian Microdata - Laura Barbieri; Mariacristina Piva; Marco Vivarelli (Institute for the Study of Labor (IZA), 2016)
This paper explores the employment impact of innovation activity, taking into account both R&D expenditures and embodied technological change (ETC). We use a novel panel dataset covering 265 innovative Italian firms over the period 1998-2010. The main outcome from the proposed fixed effect estimations is a labor-friendly nature of total innovation expenditures; however, this positive effect is barely significant when the sole in-house R&D expenditures are considered and fades away when ETC is included as a proxy for innovation activities. Moreover, the positive employment impacts of innovation activities and R&D expenditures are totally due to firms operating in high-tech industries and large companies, while no job-creation due to technical change is detectable in traditional sectors and SMEs.
Keywords: O31; O33; 330; technology; innovation; R&D; embodied technological change; employment